Numerical relativity simulations of the neutron star merger GW190425: microphysics and mass ratio effects. Issue 4 (26th August 2022) - Camilletti, Alessandro; Chiesa, Leonardo; Ricigliano, Giacomo; Perego, Albino; Lippold, Lukas Chris; Padamata, Surendra; Bernuzzi, Sebastiano; Radice, David; Logoteta, Domenico; Guercilena, Federico Maria
ABSTRACT: GW190425 was the second gravitational wave (GW) signal compatible with a binary neutron star (BNS) merger detected by the Advanced LIGO and Advanced Virgo detectors. Since no electromagnetic counterpart was identified, whether the associated kilonova was too dim or the localization area too broad is still an open question. We simulate 28 BNS mergers with the chirp mass of GW190425 and mass ratio 1 ≤ q ≤ 1.67, using numerical-relativity simulations with finite-temperature, composition dependent equations of state (EOS) and neutrino radiation. The energy emitted in GWs is 0.083 M_c^2 with peak luminosity of 1.1–2.4× 10^58/(1+q)^2 erg s^-1 . Dynamical ejecta and disc mass range between 5 × 10 −6 –10 −3 and 10 −5 –0.1 M_, respectively. Asymmetric mergers, especially with stiff EOSs, unbind more matter and form heavier discs compared to equal mass binaries. The angular momentum of the disc is 8–10 M_ GM_disc/c over three orders of magnitude in M disc . While the nucleosynthesis shows no peculiarity, the simulated kilonovae are relatively dim compared with GW170817. For distances compatible with GW190425, AB magnitudes are always dimmer than ∼20 mag for the B, r, and K bands, with brighter kilonovae associated to more asymmetric binaries and stiffer EOSs. We suggest that, even assuming a good coverage of GW190425's sky location, the kilonova could hardly have been detected by present wide-field surveys and no firm constraints on the binary parameters or EOS can be argued from the lack of the detection.